2019
DOI: 10.5539/jel.v8n5p125
|View full text |Cite
|
Sign up to set email alerts
|

Association of Career Satisfaction with Stress and Depression: The Case of Preservice Music Teachers

Abstract: In order to investigate the relationships between preservice music teachers’ levels of career satisfaction, severity of depression, and perceived stress, ninety-four students enrolled in the music education BSc program of the faculty of education at a public university in southwestern part of Turkey were survey. Data were collected by Beck’s Depression Inventory, Perceived Stress Scale, and Career Satisfaction Scale. Associations were analyzed by ANOVA, Pearson’s product-moment co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Recent studies have suggested that the psychosocial work environment of musicians may be considered more demanding than that of other occupations (Holst et al, 2012;Burak and Atabek, 2019;Détári et al, 2020;Musgrave and Gross, 2020). For example, Vaag et al (2016) reported that, compared to the general population, professional musicians had more symptoms of anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that the psychosocial work environment of musicians may be considered more demanding than that of other occupations (Holst et al, 2012;Burak and Atabek, 2019;Détári et al, 2020;Musgrave and Gross, 2020). For example, Vaag et al (2016) reported that, compared to the general population, professional musicians had more symptoms of anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…The creative industries have been described by a high degree of occupational stress (Wills and Cooper, 1987 ; Middlestadt and Fishbein, 1988 ; Smith et al, 2000 ; Iñesta et al, 2008 ; Gross and Musgrave, 2020 ), and recent studies have suggested that the psychosocial work environment of musicians are more demanding than in most other occupations (Holst et al, 2012 ; Burak and Atabek, 2019 ; Detari et al, 2020 ; Gross and Musgrave, 2020 ). In addition to the industry being described as potentially harmful, there are also studies indicating vulnerability at the individual level.…”
Section: Introductionmentioning
confidence: 99%
“…They described the stress levels among the employed population aged from 18 to 75 and examines the associations between stress and depression [17]. The positive relation found between high levels of general day-to-day stress and low levels of co-worker support was associated with higher odds of depression [18,19]. Similarly, Shields and Margot Examined a positive relationship found between academic stress and depression among college students [20].…”
Section: Literature Reviewmentioning
confidence: 99%